Development of Buddhist and cultural learning centers in Kantharawichai District MahaSarakham Province - Lanwong, Adun; (Surachit Kachit), PhrakhruAnukunpariyattikan; (Prakas Chaiyarat), Phrakhrusiripariyatbandit; Chayapipu, PhrapaladTinnapon; (Putawung), PhramahaSurasak Phuriko; Ployngam, Jansiri (Journal of Graduate MCU KhonKaen Campus, 2025)
This research article aims to 1) to study the current condition of learning resources in Kantharawichai District, Mahasarakham Province 2) To propose guidelines for developing Buddhist and cultural learning resources in Kantharawichai District, Mahasarakham Province Using qualitative research methods by studying information from 2 learning sources: 1) Wat Phuttha Mongkol, Khanthararat Subdistrict, 2) Suwanawat Temple, Khok Phra Subdistrict, and by conducting in-depth interviews with 30 person. The research results found that; 1. Learning resources in the area of Kantharawichai District, Maha Sarakham Province, consist of 2 places: 1) Wat Phutthamongkhon Community Learning Resource, Khanthararat Subdistrict. This learning resource has the highlight of the Phutthamongkhon Standing Buddha, a sandstone Buddha image in the Dvaravati art style, which is more than 1,400 years old. 2) Wat Suwannawat Community Learning Resource, Khok Phra Subdistrict, Kantharawichai District, Maha Sarakham Province, is a learning resource for Buddhist art, consisting of 2 things: 1) Phra Phuttha Ming Mueang 2) Ancient Sim. 2. Guidelines for the development of Buddhist and cultural learning resources in Kantharawichai District, Maha Sarakham Province, found that 1) The development of Buddhist and cultural learning resources resulted from community participation. Local administrative organizations were open to hearing opinions and acting as consultants, jointly thinking, working, and developing with the community. 2) The development of Buddhist and cultural learning resources in Kantharawichai District, Maha Sarakham Province, has value and influence on the way of life of local people, namely (1) identity, (2) education, (3) economy, (4) society, causing people in the community and society to define roles and responsibilities of individuals to create peace and happiness, reflecting the beliefs of people in the past in various aspects that are seen in the art of Buddhist art. It also aroused the consciousness of people in the community to love and cherish in helping to preserve this valuable heritage to continue with the community.